2013
DOI: 10.1371/journal.pone.0072310
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Drug Use Is a Significant Risk Factor for Loss to Follow Up in Patients with HIV-1 Infection at a Large Urban HIV Clinic in Tokyo

Abstract: BackgroundLoss to follow up (LTFU) is an important prognostic factor in patients with HIV-1 infection. The impact of illicit drug use on LTFU of patients with HIV-1 infection is unknown in Japan.MethodsA single center observational study was conducted to elucidate the impact of illicit drug use on LTFU at a large HIV clinic in Tokyo. LTFU was defined as those who discontinued their visits to the clinic for at least 12 months and were not known to be under the care of other facilities or have died within 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…One study using data from 18 sites in the Asia–Pacific region reported an LTFU rate of 21.4 per 100 person-years, although around half of them had temporal LTFU [ 13 ]. Another study from Japan found an LTFU rate of 2.49 per 100 person-years [ 14 ]. Although the definition of LTFU varied between our study and previous studies, it is reasonable to conclude that the rate of retention in our study is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…One study using data from 18 sites in the Asia–Pacific region reported an LTFU rate of 21.4 per 100 person-years, although around half of them had temporal LTFU [ 13 ]. Another study from Japan found an LTFU rate of 2.49 per 100 person-years [ 14 ]. Although the definition of LTFU varied between our study and previous studies, it is reasonable to conclude that the rate of retention in our study is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…20 Because the interview could underestimate the prevalence of illicit drug use, we also searched the medical records for information on illicit drug use and related variables covering the period from the first visit to December 2012.…”
Section: Measurementsmentioning
confidence: 99%
“…Furthermore, Japan has an efficient public transportation network. Despite these circumstances, some reports [14] [15] [16] have shown that approximately 5% to 10% of patients who are infected with HIV discontinue medical care in Japan. In this study, we clarified factors that led to the discontinuation of medical care among HIV patients in Japan by analyzing data from interviews.…”
Section: Introductionmentioning
confidence: 99%
“…15) Trust in the medical staff: Participants discussed their relationship with Health the medical staff in which they had good rapport with their primary doctor or nurses at the hospital. 16) Relationship with and trust in the primary doctor: Participants discussed having conversations with their primary doctor or having trust in their primary doctor.…”
mentioning
confidence: 99%
See 1 more Smart Citation